Aplikasi SMSGateway Dengan Sistem Broadcast Untuk Pengecekan Absensi Dan Nilai Siswa - Supriyono, Supriyono (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2015)
During this students' parents are very limited in monitoring the activities sons and daughters academic year, starting from the academic attendance tees sons and daughters. That sometimes surprising students' parents because the children's academic they decreased and there are also those who got a letter of reprimand because on their children. Thus I make application attendance list and checking the London-based Slatri SMS Gateway at SDN 03 Slatri that troubleshoots able to help parents of students in monitoring the activities to learn their childrens' schools effective. SMS application Gateway was built using programming language Java. While for database using MySQL. This application use system broadcast the attendance list and values will be send to parents to standards of the school without parents